Influence of pitch modulation on event-related potentials elicited by Dutch word stimuli in a brain–computer interface language rehabilitation task - Kojima, Simon; Eren Kortenbach, Benjamin; Aalberts, Crispijn; Miloševska, Sara; de Wit, Kim; Zheng, Rosie; Kanoh, Shin’ichiro; Musso, Mariacristina; Tangermann, Michael (Journal of neural engineering, 2025)
Objective. Recently, a novel language training using an auditory brain–computer interface (BCI) based on electroencephalogram recordings has been proposed for chronic stroke patients with aphasia. Tested with native German patients, it has shown significant and medium to large effect sizes in improving multiple aspects of language. During the training, the auditory BCI system delivers word stimuli using six spatially arranged loudspeakers. As delivering the word stimuli via headphones reduces spatial cues and makes the attention to target words more difficult, we investigate the influence of added pitch information. While pitch modulations have shown benefits for tone stimuli, they have not yet been investigated in the context of language stimuli. Approach. The study translated the German experimental setup into Dutch. Seventeen native Dutch speakers participated in a single session of an exploratory study. An incomplete Dutch sentence cued them to listen to a target word embedded into a sequence of comparable non-target words while an electroencephalogram was recorded. Four conditions were compared within-subject to investigate the influence of pitch modulation: presenting the words spatially from six loudspeakers without ( 6D ) and with pitch modulation ( 6D-Pitch ), via stereo headphones with simulated spatial cues and pitch modulation ( Stereo-Pitch ), and via headphones without spatial cues or pitch modulation ( Mono ). Main results. Comparing the 6D conditions of both language setups, the Dutch setup could be validated. For the Dutch setup, the binary AUC classification score in the 6D and the 6D-Pitch condition were 0.75 and 0.76, respectively, and adding pitch information did not significantly alter the binary classification accuracy of the event-related potential responses. The classification scores in the 6D condition and the Stereo-Pitch condition were on the same level. Significance. The competitive performance of pitch-modulated word stimuli suggests that the complex hardware setup of the 6D condition could be replaced by a headphone condition. If future studies with aphasia patients confirm the effectiveness and higher usability of a headphone-based language rehabilitation training, a simplified setup could be implemented more easily outside of clinics to deliver frequent training sessions to patients in need.